2018
DOI: 10.1007/s11157-018-9466-1
|View full text |Cite
|
Sign up to set email alerts
|

The molecular processes of urea hydrolysis in relation to ammonia emissions from agriculture

Abstract: Ammonia emissions from the agricultural sector give rise to numerous environmental and societal concerns and represent an economic challenge in crop farming, causing a loss of fertilizer nitrogen. Ammonia emissions from agriculture originate from manure slurry (livestock housing, storage, and fertilization of fields) as well as urea-based mineral fertilizers. Consequently, political attention has been given to ammonia volatilization, and regulations of ammonia emissions have been implemented in several countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(160 citation statements)
references
References 146 publications
(160 reference statements)
5
152
1
2
Order By: Relevance
“…Application of urea for 25 yr was reported to decrease the pH of calcareous soil by 0.9 units (Zhang et al, 2017). Urea hydrolyzes to NH 4 + under the catalysis of urease (Sigurdarson et al, 2018). The roots secret H + when the crops absorb NH 4 + , resulting in an imbalance of Ca 2+ , Mg 2+ , and H + on the surface of soil colloidal particles and inducing soil acidification (Zhang et al, 2017).…”
Section: Soil Ph and Organic Matter Distribution With Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of urea for 25 yr was reported to decrease the pH of calcareous soil by 0.9 units (Zhang et al, 2017). Urea hydrolyzes to NH 4 + under the catalysis of urease (Sigurdarson et al, 2018). The roots secret H + when the crops absorb NH 4 + , resulting in an imbalance of Ca 2+ , Mg 2+ , and H + on the surface of soil colloidal particles and inducing soil acidification (Zhang et al, 2017).…”
Section: Soil Ph and Organic Matter Distribution With Depthmentioning
confidence: 99%
“…The difference in soil Olsen P was determined with respect to depth and land use ( Table 2). The critical agronomic P values as indicators for crop P deficiency and P excess are 20 and 40 mg kg −1 Olsen P in calcareous soil, respectively (Shen, 1998). Based on these critical values of topsoil Olsen P, 79.2% of agricultural land is at risk of P excess and 12.5% at risk of P deficiency.…”
Section: Soil Olsen Phosphorus Distribution With Depthmentioning
confidence: 99%
“…(Bekheet & Syrett, ; Booth & Vishniac, ; Cook, ; Frankenberger & Tabatabai, ; Hanlon, ; Sumner, ) Urease in livestock animal feces is a concern in agriculture because it hydrolyzes the urea found in livestock animal urine, causing emissions of NH 3 that can damage the environment, reduce air quality, and represent a loss of fertilizer nitrogen. (Sigurdarson et al, ) Urease is also an important virulence factor of several pathogens. The pathogenic ureolytic bacterium Proteus mirabilis can infect the urinary tract and cause complications such as the formation of kidney or bladder stones, which is a direct result of ureolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Independent hydroanalysis of AdBlue samples concluded that increasing value of conductivity is a cause of increasing concentration of carbonate ions and ammonia. It is known from the literature that urea can hydrolyse forming cyanatanes and consequently carbonate ions and ammonia . The subsequent considerable decrease in the electrical conductivity with runtime in the case of Test 1 (spraying), where the AdBlue solution is in intensive contact with air, could be attributed to the decomposition of ammonium carbonate.…”
Section: Resultsmentioning
confidence: 98%
“…It is known from the literature that urea can hydrolyse forming cyanatanes and consequently carbonate ions and ammonia. 13,23 The subsequent considerable decrease in the electrical conductivity with runtime in the case of Test 1 (spraying), where the AdBlue solution is in intensive contact with air, could be attributed to the decomposition of ammonium carbonate. Changes in alkalinity of AdBlue (expressed as a mass concentration of ammonia) during the tests of SCR systems clearly illustrate increasing concentration of ammonia due to undergoing chemical conversion of urea.…”
Section: Tracking Adblue Properties During Tests Of Scr Systemsmentioning
confidence: 99%